2011
DOI: 10.3109/10715762.2011.637203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of passive stretch on intracellular nitric oxide and superoxide activities in single skeletal muscle fibres: Influence of ageing

Abstract: Skeletal muscle is repeatedly exposed to passive stretches due to the activation of antagonist muscles and to external forces. Stretch has multiple effects on muscle mass and function, but the initiating mechanisms and intracellular signals that modulate those processes are not well understood. Mechanical stretch applied to some cell types induces production of reactive oxygen species (ROS) and nitric oxide that modulate various cellular signalling pathways. The aim of this study was to assess whether intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 39 publications
4
25
0
Order By: Relevance
“…Indeed, using a similar system, Ping et al [2017] showed that ROS, NADPH oxidase 1, and protein disulfide isom- erase may determine the fate of stretched vascular smooth muscle cells [Ping et al, 2017]. Passive mechanical stretch of a muscle cell may generate ROS, which are required for proliferation and differentiation of muscle cells [Palomero et al, 2012]. Under physiological conditions, these ROS are balanced by ROS scavengers so that appropriate levels of ROS are maintained to facilitate cell proliferation [Bigarella et al, 2014;Kozakowska et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, using a similar system, Ping et al [2017] showed that ROS, NADPH oxidase 1, and protein disulfide isom- erase may determine the fate of stretched vascular smooth muscle cells [Ping et al, 2017]. Passive mechanical stretch of a muscle cell may generate ROS, which are required for proliferation and differentiation of muscle cells [Palomero et al, 2012]. Under physiological conditions, these ROS are balanced by ROS scavengers so that appropriate levels of ROS are maintained to facilitate cell proliferation [Bigarella et al, 2014;Kozakowska et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…Muscle stretching may also reduce blood flow and tissue oxygen availability, causing an accumulation of metabolic end products and/or reactive oxygen and nitrogen species (Palomero et al 2012). In animal studies, passive stretching has increased nitric oxide (Tidball et al 1998) and reactive oxygen species (Palomero et al 2012) production.…”
Section: Stretch-induced Contractile "Fatigue" or Damagementioning
confidence: 99%
“…In animal studies, passive stretching has increased nitric oxide (Tidball et al 1998) and reactive oxygen species (Palomero et al 2012) production. No direct measurements have been made in humans; however, Trajano and colleagues (2014) observed that intermittent stretching (15 s rest between 5 stretches of 1 min each) caused notable perfusion and reperfusion of plantar flexor muscles and a greater magnitude of and longer-lasting force loss than did the same volume of continuous stretching, even though the absolute level of deoxygenation was greater during continuous stretches.…”
Section: Stretch-induced Contractile "Fatigue" or Damagementioning
confidence: 99%
“…Many of the features of X-ROS signaling in the heart are also found in skeletal muscle (38,51), but the signaling involves additional molecular components (38). One prominent new component in skeletal muscle is a calcium-conducting sarcolemmal ''transient receptor potential'' (TRP) channels (2,6,18,48,82) whose opening is enhanced by Nox2-derived ROS (Fig.…”
Section: X-ros Signaling: Mechanotransduction-activated Nox2-dependenmentioning
confidence: 99%